PENGARUH SENAM OTAK (BRAIN GYM) TERHADAP FUNGSI KOGNITIF PADA LANSIA DI RT 03 RW 01 KELURAHAN TANDES SURABAYA - Yuliati, Yuliati; Hidaayah, Nur; Hidaayah, Nur (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Decline in cognitive function in the elderly is not considered reasonable, and can be inhibited with brain gym activity.The purpose of this study is to investigate the influence of brain exercise on cognitive function in the elderly in RT 03 RW 01 Tandes Village. Design of this study Pre-Experiment with one grop pre post test,the population are from ten of elderly aged 60-74 years. Sampling by simple random sampling, gained 6 people. The independent variable is the gymnastics of the brain and the dependent variable is a function cognitive. The data colledted by using the MMSE tabulation of data editing, coding, processing, celaning, tabulating and analyzed by Wilcoxon Sign Rank with α = 0.05. The results showed that prior to the brain gym majority (66.7%) had moderate cognitive impairment after brain gym majority (66.7%) are not impaired cognitive function. After the Wilcoxon signed rank test obtained value ρ = 0.014 <α = 0.05 so that H0 is rejected, it means that there is the influence of brain exercise on cognitive function in the elderly. Conclusions from this research is the brain exercises can improve cognitive function in the elderly in RT 03 RW 01 Tandes village. Brain gym should be applied in Posyandu every 3 times a week as more routine brain exercise in the elderly, then cognitive function will be increased, then can make the decline in function cognitive slowly.